2012
DOI: 10.3402/tellusb.v64i0.10961
|View full text |Cite
|
Sign up to set email alerts
|

Sources and sinks of CO<sub>2</sub> in the west coast of Bay of Bengal

Abstract: A B S T R A C TObservations at high spatial resolution (100 )50 km 2 ) in the western continental shelf of Bay of Bengal during southwest monsoon, when peak discharge occurs into the Bay through major rivers of the Indian subcontinent, revealed that freshwater discharge exerts dominant control on the inorganic carbon components in surface waters. Lower than present atmospheric pCO 2 levels were found in the northwestern (NW) than southwestern (SW) coastal Bay of Bengal. The pCO 2 levels in the peninsular river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…Recently, Sarma et al (2015) reported coastal water acidification due to increased anthropogenic aerosol loading in the northern BoB in winter and spring during recent decades, and the pH of the coastal waters decreased at the rate of 0.007 units yr À 1 , which was 2-3 times higher than that of elsewhere in the world. Sarma et al (2012b) reported that the direction of CO 2 flux (source or sink) from the coastal western BoB was dependant on the characteristics of the discharged water from the rivers. They further noted that the coastal regions influenced by the peninsular rivers were the strong net source while glacial river, the Ganges, was a net sink for atmospheric CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sarma et al (2015) reported coastal water acidification due to increased anthropogenic aerosol loading in the northern BoB in winter and spring during recent decades, and the pH of the coastal waters decreased at the rate of 0.007 units yr À 1 , which was 2-3 times higher than that of elsewhere in the world. Sarma et al (2012b) reported that the direction of CO 2 flux (source or sink) from the coastal western BoB was dependant on the characteristics of the discharged water from the rivers. They further noted that the coastal regions influenced by the peninsular rivers were the strong net source while glacial river, the Ganges, was a net sink for atmospheric CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…They further noted that the coastal regions influenced by the peninsular rivers were the strong net source while glacial river, the Ganges, was a net sink for atmospheric CO 2 . It was hypothesized that decreased river discharge, either due to weak intensity of the monsoon or dam regulation of freshwater release, would decrease pCO 2 levels and acidification in the coastal BoB and therefore decreases the CO 2 flux to atmosphere (Sarma et al, 2012b). On the contrary, weakening of stratification would promote upwelling and in turn would increase the pCO 2 levels and acidification in the coastal BoB.…”
Section: Introductionmentioning
confidence: 99%
“…This is recognized as a challenging area to capture the physical and biogeochemical responses related to both the role of the monsoon and the significant amount of discharge from the major rivers such as Ganges, Brahmaputra, Godavari, etc., with variable characteristics of an inorganic carbon system. Recently Sarma et al (2012) observed that whether coastal Bay of Bengal acts as a source or sink may depend on the characteristics of the discharge water received by the coastal zone; in many cases, the current OBGMs either do not incorporate freshwater river inputs at all or treat the lateral river boundary condition as the addition of freshwater only without incorporating explicit water chemistry (dissolved inorganic carbon, alkalinity). The OBGMs underestimated the discharge by as much as 50 % (Dia and Trenberth, 2002).…”
Section: Northern Indian Ocean (Nio; 18 • S-30 • N)mentioning
confidence: 99%
“…The northeastern region (Bay of Bengal) receives a significant amount of freshwater and is strongly stratified compared to the northwestern Indian Ocean, leading to contrasting behavior in physical processes and biogeochemical cycling (George et al, 1994). Consequently, the northeastern Indian Ocean acts as a mild net sink of atmospheric CO 2 , whereas the northwestern Indian Ocean acts as a net source Sarma, 2003;Takahashi et al, 2009;Valsala and Maksyutov, 2010a;Sarma et al, 2012). The pCO 2 in this region shows large seasonal variations associated with the monsoonal circulation, with maxima during summer and winter and minima in the transition periods (Sarma et al, 1998(Sarma et al, , 2000(Sarma et al, , 2012Goyet et al, 1998;Sarma et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggest that the coastal Bay of Bengal acts as a source for atmospheric CO 2 throughout the year except for some monsoon months [8], [9]. However, the source/sink nature and its magnitude is mainly regulated by the riverine influx and east Indian coastal current [10]. The work reported here was aimed to quantify the summer CO 2 flux in the riverine and near shore waters of Mahandi estuary and to evaluate the environmental control on CO 2 flux.…”
Section: Introductionmentioning
confidence: 99%